Effects of plant growth-promoting bacteria on soil dehydrogenase activity and turfgrass aesthetics during early growth - Truba, Milena M.; Kulkova, Iryna; Sosnowski, Jacek; Dobrzyński, Jakub (Journal of Water and Land Development, 2026)
This study evaluated the effects of a microbial inoculant containing plant growth-promoting bacteria (PGPB) on soil microbial properties and turfgrass aesthetic quality under limited irrigation. The experiment was conducted on two turfgrass systems: a perennial ryegrass (Lolium perenne L.) (T1) and a mixture including microclover (T2), under two soil moisture levels: 40 and 60% field water capacity (FWC). The parameters analysed included regrowth intensity, root length-to-dry-mass ratio, soil-plant analysis development (SPAD) leaf greenness index, and soil dehydrogenase activity (DHA). PGPB application significantly increased both root system length and biomass, particularly under drought stress, which was also reflected in higher DHA values and improved turf visual quality. The highest dehydrogenase activity was recorded in PGPB-treated plots at 60% FWC, regardless of turf type. Although SPAD index differences were not statistically significant, a consistent trend indicated that PGPB application under drought conditions helped stabilise SPAD values. The best visual quality was observed in the perennial ryegrass and microclover mixture, likely due to a more developed root system and enhanced microbial activity in the rhizosphere. These findings suggest that PGPB application at the beginning of the growing season can enhance turf resilience and recovery under drought stress.